Synthesis and analgesic, anti-inflammatory activities of some novel Thiadiazole derivatives (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A series of novel 1,3,4-thiadiaoles was synthesized and investigated for in vivo analgesic and in vivo anti-inflammatory activity. The structures of all synthesized compounds were confirmed by means of elemental analysis, IR, 1H NMR, and LCMS. All compounds were evaluated for their analgesic and anti-inflammatory activities by tail-flick method and carrageenan-induced rat paw edema test, respectively. Among all the synthesized compounds, compounds 3d and 3e exhibited the most prominent and consistent anti-inflammatory activity. In acute ulcerogenicity study, it can be concluded that these compounds are devoid of the deadlier gastrointestinal toxicities.